Una nueva mirada a la expansión del derecho penal (2017)
The purpose of this text is to propose a new approach to the analysis of the expansion of criminal law. We study essentially what Jesus María Silva Sánchez said in his text "The expansion of criminal law: Aspects of criminal policy in postindustrial societies". Therefore, we will first present some preliminary considerations to explain in depth some important aspects about the punitive power of the state, and consequently we are going to explain the reasons we believe have fostered the expansion of criminal law. Then, we will outline the dogmatic responses that have been given to respond to this phenomenon. And, finally, we will make some considerations regarding the expansion of criminal law in Colombia and the ways in which it can be solved, as well as reflect on the need to foster a deep public and political debate on the subject.